A Culturally Targeted Website for Hispanics/Latinos About Living Kidney Donation and Transplantation: A Randomized Controlled Trial of Increased Knowledge. Issue 5 (May 2016) - Gordon, Elisa J.; Feinglass, Joe; Carney, Paula; Vera, Karina; Olivero, Maria; Black, Anne; O'Connor, Kate; MacLean, Jessica; Nichols, Shari; Sageshima, Junichiro; Preczewski, Luke; Caicedo, Juan Carlos
Abstract : Background: Hispanics/Latinos receive disproportionately fewer living donor kidney transplantations (LDKTs) than non-Hispanic whites. We conducted a multisite, randomized controlled trial to evaluate the efficacy of exposure to a bilingual, culturally targeted website, Infórmate, for increasing Hispanics' knowledge about LDKT. Methods: Hispanic patients initiating transplant evaluation and their family/friends at 2 transplant centers were randomized to view Infórmate before attending routine transplant education sessions; usual care controls only attended education sessions. All participants completed a pretest; website participants also completed a posttest immediately after viewing Infórmate . All participants completed a 3-week telephone follow-up test. Random effects linear regression of 3-week knowledge scores tested the significance of website exposure after adjusting for clustering within families and controlling for pretest scores and covariates. Results: Two hundred-eighty-two individuals participated (81% patient participation rate). Website exposure was associated with a mean 21.7% same day knowledge score increase between pretest and posttest ( P < 0.001). At 3 weeks, website participants' knowledge scores remained 22.6% above the pretest; control scores increased to 11.8% ( P = 0.0001). Regression results found that website participants were associated with a 10.0% greater knowledge score at 3-week follow-up ( P < 0.0001). Most website participants (92.6%) plan to return to Infórmate in the future. Conclusions: Our culturally targeted website increased participants' knowledge about LDKT above and beyond transplant education and should supplement transplant center education for Hispanics. When considered at the population level, Infórmate could have a great impact on knowledge gains in this underserved population disproportionately affected by kidney disease. Abstract : This randomized study shows that Info´ rmate, a culturally targeted website for Hispanics, increases participants' knowledge about living donor kidney transplantation beyond usual transplant education for Hispanics. Supplemental digital content is available in the text.